2004
DOI: 10.1002/anie.200461011
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic–π Interactions Stabilize a Self‐Assembled As2L3 Supramolecular Complex

Abstract: The self-assembly of supramolecular coordination compounds has resulted in structures with a diverse range of properties, shapes, sizes, and stoichiometries, including helicates (M 2 L 2 , M 2 L 3 , etc.), triangles (M 3 L 3 ), squares (M 4 L 4 ), rings (e.g., M 6 L 6 ), and polyhedra (M 4 L 4 , M 4 L 6 , M 6 L 6 , M 8 L 12 , etc.).[1] These assemblies almost exclusively contain metals with square-planar, tetrahedral or octahedral coordination geometries. Metals that can exhibit more peculiar coordination geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 36 publications
4
84
0
Order By: Relevance
“…The As-S bonds in 1 range from 2.23 Å to 2.29 Å . There are no intramolecular As-p interactions, despite the fact that As-p interactions are a well known characteristic of As-aromatic systems [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The As-S bonds in 1 range from 2.23 Å to 2.29 Å . There are no intramolecular As-p interactions, despite the fact that As-p interactions are a well known characteristic of As-aromatic systems [3].…”
Section: Discussionmentioning
confidence: 99%
“…Recent interest in arsenic thiolates as building blocks in self-assembled macrocycles [2,3] along with a lack of single crystal X-ray structural analysis of relatively simple arsenic thiolates has prompted our work on the synthesis and characterization of several arsenic dithiolates [4]. These are of the general formula RS 2 AsX where R is an organic group connecting the sulfurs and X = Cl or I.…”
Section: Introductionmentioning
confidence: 99%
“…[27, 34] More generally our study is a contribution to highlight and rationalize further subtle factors affecting the coordination geometry of heavy main group elements in proteins and supramolecular systems. Indeed, in the process of developing new supramolecular coordination compounds, Johnson and collaborators have already thoroughly explored the role played by weak attractive forces, such as As···π interactions and secondary bonding interactions, in trigonal-pyramidal As(III) complexes, [28b] demonstrating that such interactions can dramatically affect the coordination geometry of As(III) in thiolate complexes. [28a, 50] In particular, while exohedral coordination is generally observed in As(III) compounds, the intramolecular As···π interactions in As 2 (L) 3 and As 2 (L) 2 Cl 2 complexes in which L is an aromatic ligand was shown to induce endohedral directionality of the As(III) stereochemically active lone pair.…”
Section: Discussionmentioning
confidence: 99%
“…[24] The preference of trigonal-pyramidal thiolate structures by As(III) with small molecules [24e, 25] and in proteins [26] is further proven by a recent crystal structure of the designed three-stranded coiled coil As( CS L9C) 3 by Touw et al [2627] Crystal structures of ArsD and ArsR have not yet been reported to explain the exact mode of As coordination, however, an exo-conformation (shown in scheme 1) 1 of AsS 3 was speculated based on the crystal structure of synthetic small molecules with aromatic rings or chelated alkyl dithiolates. [25] In contrast, Johnson and coworkers (using small molecules) [28] and Pecoraro and coworkers (using designed 3-strand coiled coil peptides) [27] discovered that the orientation of the lone pair could influence the As(III) to adopt an endo conformation. The As( CS L9C) 3 [PDB code 2JGO] was the first example that directly mimicked the coordination environment of As(III) in ArsR and ArsD.…”
Section: Introductionmentioning
confidence: 99%
“…The complicacies and sophistication of self-assembly process is due to the presence of various possible interactions which can lead to many ways of assembling the building blocks. Usually the strength of these possible interactions also come in a wide range including strong covalent force, intermediate coordinative force [4][5][6][7] and various weak forces such as hydrogen bonding [8][9][10][11][12][13][14], pÁÁÁp interaction [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], C-HÁÁÁp interaction [31,32], metalÁÁÁp [33][34][35][36][37][38], anionÁÁÁp interaction [39] and lone pairÁÁÁp interaction [40][41][42][43][44][45][46][47][48]. The existence of phenomena like polymorphism [49][50]…”
Section: Introductionmentioning
confidence: 99%